Pour un engagement cosmopolite et séquentiel : à propos d’une recherche sociologique sur les médias et le conflit israélo-palestinien - Jérôme Bourdon (Argumentation et Analyse du Discours, 2015)
This article tries to draw general lessons from the personal and professional itinerary of a media sociologist working on the coverage of the Israeli-Palestinian conflict. It starts with a discussion of Heinich’s plea (2002) for an “engaged neutrality”, based on a distinction between the positions of researcher, thinker and expert, to which this article adds the position of teacher. It also claims that Heinich’s ideal of neutrality is hard to fulfill when working on a “hot topic” which triggers vivid and public controversies, involving notably journalists who have a complicated relation with researchers. Finally, it insists on the fact that the different positions “have a passport”, a cultural identity, which matters especially for topics which have a transnational dimension, and controversies which opposes actors following lines of identity and nation. In the case of the Israeli-Palestinian conflict, the media have been the target of much criticism for their bias in being supposedly engaged in favor of one side or the other, depending on the periods and the countries. As researcher, the author claims it is difficult, scientifically, to take sides in the controversy, and that it is also useless as it leads to a replication of the actors’ discourse. He follows a principle of neutrality, by trying to explain (not to judge) the trajectories and the positions of the actors (three groups: the media critics and “monitors”, the journalists they accuse, and the diverse, diasporic audience of the media). The commitment (engagement) of the author comes at the end of his work: it is directed at the journalists (especially as future journalists/students) when they ignore their specific responsibility and identities, holding a neutral discourse while they should expose their own implication and take into account the reaction of the public. It also targets their audiences, who are invited to understand better (and then overcome) their emotional implications in the images of the conflict. This approach is not without (minor) risks: some actors will summon you to give up on neutrality and choose your side, others will unmask you for “ultimately” working for one side or the other, and, most dangerously, some will ignore you because you do not want to join the controversy.